Recovery and regeneration of LiCoO2-based spent lithium-ion batteries by a carbothermic reduction vacuum pyrolysis approach: Controlling the recovery of CoO or Co. (September 2019) - Tang, Yiqi; Xie, Hongwei; Zhang, Beilei; Chen, Xiang; Zhao, Zhuqing; Qu, Jiakang; Xing, Pengfei; Yin, Huayi
Highlights: The optimal vacuum pyrolysis peeling temperature is 673–723 K. The pyrolyzed products can be tailored by tuning temperature and C/LiCoO2 ratio. The Li and Co extraction rates are over 93% and 99%. CoO was exclusively obtained when the C/LiCoO2 ratio is lower than 1/15 at 923 K. The regenerated LiCoO2 delivers a capacity of 145 mAh g −1 at 0.5C. Abstract: An environmentally benign vacuum pyrolysis (VP) approach is employed to recover Li and Co from spent LiCoO2 -based lithium-ion batteries (LIBs). First, the electroactive materials were separated from the current collector by the VP method from 623 to 823 K with an attempt to choose an appropriate temperature. Then, the as-received cathode materials were mixed with different amounts of graphite from the anode to selectively convert LiCoO2 to Co or CoO and Li2 CO3 by carbothermic reduction under vacuum and at 873 to 1273 K. After carbothermic reduction, the pyrolyzed powder was leached in water to separate Li2 CO3 from Co/CoO. By alternating the C/LiCoO2 mass ratio and the pyrolysis temperature, a recovery rate reaches over 93% for Li and 99% for Co. Finally, the recovered CoO and Li2 CO3 were used to regenerated LiCoO2 that delivered a specific capacity of 145 mAh g −1 at 1C and retaining 93% of the initial capacity after 100 cycles. Overall, a multi-vacuum-pyrolysis approach offers a closed-loop route for the management of spent LIBs without using any hazardous chemicals.